2023
DOI: 10.1037/str0000272
|View full text |Cite
|
Sign up to set email alerts
|

Associations between long-term and near-term stressful life events, suicide crisis syndrome, and suicidal ideation.

Abstract: The suicide crisis syndrome (SCS) and suicidal ideation (SI) are differentially linked to short-term suicide risk. Since both are theoretically and empirically linked to stressful life events, which have increased during the COVID-19 pandemic, a clear understanding of these processes may be essential for suicide prevention. Thus, the present study examined (a) associations between SCS, SI, and total number of stressful life events and (b) relations between specific types of stressful life events, SCS, and SI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…41,42 Our results are also consistent with SCS research specifically, such that SCS occurs crossnationally 43 and is associated with personal stressors incurred during the first year of the pandemic. 10,44 Finally, our results held up after controlling for sex, age, and college education, factors that varied widely across countries in our sample. In sum, our findings show that at both the country and individual levels of analysis, the severity of exposure to pandemic parameters is associated with increased suicidal risk.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…41,42 Our results are also consistent with SCS research specifically, such that SCS occurs crossnationally 43 and is associated with personal stressors incurred during the first year of the pandemic. 10,44 Finally, our results held up after controlling for sex, age, and college education, factors that varied widely across countries in our sample. In sum, our findings show that at both the country and individual levels of analysis, the severity of exposure to pandemic parameters is associated with increased suicidal risk.…”
Section: Discussionmentioning
confidence: 53%
“…24,[27][28][29] Furthermore, SCS symptoms were more tightly linked to stressful life events experienced during the pandemic than were SI. 10 Suicide Risk During the Pandemic Unsurprisingly, a number of studies have shown an increase in suicide risk during the pandemic. 3,7,8 Likewise, in a large (N = 24 378) online, cross-sectional survey study of Chinese university students, mandatory quarantined status was positively associated with self-harm/suicidal ideation (OR = 4.98).…”
Section: The Suicide Crisis Syndrome (Scs)mentioning
confidence: 99%
“…Therefore, the study group seems to have succeeded in providing a good clinical description of a syndromal presuicidal state. This appraisal is further supported by the fact that an independent working group has made a very comparable proposal to characterize an acute suicidal state: the Acute Suicidal Affective Disturbance (ASAD) described by Joiner and co‐workers (2018; see also Rogers, Cao, et al., 2023). Still, family studies and studies on the exclusion of other disorders are missing from the SCS literature by now.…”
Section: Discussionmentioning
confidence: 95%
“…Since the literature search only included studies published up to December 2022, it is important to note that more recent publications on the SCS and the Narrative‐Crisis Model were not considered in the current review (Karsen et al., 2023; Lee et al., 2023; Mitelman et al., 2023; Park et al., 2023; Rogers, Jeon, et al., 2023; Rogers, McMullen, et al., 2023; Rogers, Richards, et al., 2023; Wu et al., 2023). Among the various studies, a global collaboration (Rogers, Jeon, et al., 2023; Rogers, McMullen, et al., 2023; Rogers, Richards, et al., 2023) has to be highlighted that examined the prevalence of the Suicide Crisis Syndrome in 10 countries worldwide: It was shown that the SCS occurred cross‐nationally, with rates ranging from 3.6% (Israel) to 16.2% (Poland; Rogers, Jeon, et al., 2023; Rogers, McMullen, et al., 2023; Rogers, Richards, et al., 2023). Furthermore, participants who were older, identified as cisgender men, and were married tended to have lower rates of SCS than their respective counterparts (cf.…”
Section: Discussionmentioning
confidence: 99%
“…If so, this would indicate that demographic differences in help seeking behavior may be due to increased emotional distress during the pandemic rather than solely to longstanding barriers/facilitators to health care. Such a pre-suicidal state exists: recent research has introduced the notion of an acute state that is characterized by intense negative affect and hyperarousal and that can be triggered by stressful life events, such as the COVID-19 pandemic (Galynker, 2017;Rogers et al, 2017Rogers et al, , 2023Schuck et al, 2019). Speci cally, the Suicide Crisis Syndrome (SCS; Galynker, 2017), an acute hyperaroused, negative affect state, driven by a sense of entrapment, is predictive of imminent suicidal thoughts and behavior (Barzilay et al, 2020;Yaseen et al, 2019).…”
Section: Suicide Crisis Syndromementioning
confidence: 99%